Relações lineares e não lineares entre caracteres de desenvolvimento, produção e qualidade de Fragaria x ananassa e Capsicum chinense - Diel, Maria Inês (2020)
Fragaria x ananassa and Capsicum chinense are multiple-harvest crops with high economic importance, especially in family farms, as they have high added value and are an alternative for employment and income. The aim of this study was to estimate the direct and indirect correlation between yield and quality traits to determine which traits can be used as a criterion for increasing fruit yield and quality and to adjust nonlinear regression models to describe fruit yield of the strawberry and biquinho pepper. Data from two experiments were used, with the strawberry experiment being conducted in a randomized block design with four replications, and the treatments were four substrates, two cultivars and two transplant origins with eight plants per experimental unit. The experiment with biquinho pepper was in a randomized block design in six replications, and the treatments consisted of two cultivars and four growing seasons, with four plants per experimental unit. Nonlinear regression models were adjusted for number and mass of strawberry fruits and fruit mass for biquinho pepper. To identify the linear relationships between the variables, principal component (PCA), path analysis and canonical correlation analyzes were performed. For both cultures, the logistic model is the most appropriate, as it represents the estimates of the parameters and critical points of the model, being an important way to evaluate experiments with multiple-harvest crops. There are linear relationships between phenological characters, yield and fruit quality in strawberry. Actions and management that shorten the period until the beginning of the harvest are essential for the production of high quality fruits and larger fruits. In biquinho pepper the chemical composition is modified according to cultivar and growing season, and important relationships were found to guide genetic improvement programs for the quality of bioactive pepper compounds.